Chemical Compositions and Nutrient Degradation of Elephant Grass Silage Ensiled with Black Tea Waste - Santoso, B; Lekitoo, MN; Umiyati, Umiyati (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2007)
This study evaluated the chemical compositions and nutrient degradation during ensiling of elephant grass (Pennisetum purpureum) silage with black tea waste (BTW) addition. Four silage treatments were elephant grass (S0); elephant grass + 100 g BTW/ kg fresh matter (S1); elephant grass + 200 g BTW/kg fresh matter (S2); elephant grass + 300 g BTW/kg fresh matter. About 220 g of silage material were ensiled for 30 days at room temperature (approximately 28°C). Three replicates were prepared for each treatment. Results showed that dry matter, organic matter and crude protein contents of silages increased linearly (P<0.01) with increasing black tea waste. There were linear decreases in dry matter and crude protein degradations (P<0.01) and organic matter degradation (P<0.05) during ensiling with increased black tea waste addition. Dry matter degradation values varied from 15.03 to 30.71% and were higher than degradation value of ideal silage. It was concluded that black tea waste has potential as a silage additive to improve nutritive value and fermentation quality of elephant grass silage. (Animal Production 9(2): 160-165 (2007) Key Words: Elephant grass, black tea waste, silage additive, degradation